2020
DOI: 10.1177/1538574420980604
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Surfacer® Inside-Out® Catheter Access System to Obtain Central Venous Access in Dialysis Patients With Thoracic Venous Obstructions: Single-Center Series

Abstract: Background: Thoracic central venous obstruction (TCVO) is a common condition which can impact the ability to achieve central venous access (CVA) in patients on hemodialysis. The Surfacer® Inside-Out® Catheter Access System is designed to enable repeated right-side central venous access in patients with TCVO. Methods: We retrospectively analyzed medical records of 10 dialysis patients who presented with TCVO and underwent the Inside-Out procedure with the Surfacer System to obtain CVA between 2017 and 2020. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
(30 reference statements)
1
5
0
Order By: Relevance
“…The patency and technical success rate of the inside-out technique has exceeded 82% and 97% to 100%, respectively. 8 , 10 , 11 , 12 , 13 , 14 , 15 Therefore, considering the high technical success rate and longer patency, our results have confirmed that the S-inside-out approach for patients with TCVO will provide better catheter function than the FVC technique.…”
Section: Discussionsupporting
confidence: 73%
See 4 more Smart Citations
“…The patency and technical success rate of the inside-out technique has exceeded 82% and 97% to 100%, respectively. 8 , 10 , 11 , 12 , 13 , 14 , 15 Therefore, considering the high technical success rate and longer patency, our results have confirmed that the S-inside-out approach for patients with TCVO will provide better catheter function than the FVC technique.…”
Section: Discussionsupporting
confidence: 73%
“…Some series have reported procedure-related complications in one or two patients. 8 , 10 , 11 , 12 , 13 , 14 , 15 Hadziomerovic et al 10 reported that two of nine patients had developed pneumothorax using the inside-out technique for TCC insertion. Galas and Shahverdyan 14 reported a case series using a Surfacer commercial set (Bluegrass Vascular Technologies, San Antonio, TX) for inside-out TCC insertion in 10 patients, of whom 2 had developed pneumohemothorax during the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations